The Effectiveness of Rectal Suction Biopsy in the Diagnosis of Hirschsprung's Disease - Cemal Bilir; Mustafa Onur Öztan; Gülden Diniz; Tunç Özdemir; Ali Sayan; Gökhan Köylüoğlu (Galenos Publishing House, 2023)
Objective: In order to analyse the adequacy, sensitivity, and specificity of samples obtained with rectal suction biopsy (RSB) as the standard histopathological diagnostic method in patients with suspected Hirschsprung's disease (HD). Method: This study was carried out between November 2016 and March 2018 with 24 suspected HD patients aged 0-3 years. After calculating rectosigmoid indexes (RSIs) according to barium enema images obtained in contrast-enhanced colon graphies, patients with RSI <1 underwent RSB. Clinical features of patients, treatment options, complications, laboratory test results and radiological findings were recorded for further analyses. An expert pathologist evaluated biopsy specimens, and observations were recorded. Results: There were no ganglion cells in RSB specimens in 10 (41.6%) patients who received the diagnosis of HD later on. Ganglion cells were detected in specimens of 5 (20.8%) patients; thus, the diagnosis of HD was excluded. Inadequate or suspicious biopsy specimens for histopathological evaluation were observed in 9 (37.5%) patients. If the biopsy specimen volume was more voluminous than 4 mm3, its diagnostic sensitivity and specificity for HD were 80% and 66.67%, respectively (area under the curve=0.789); If the submucosa/mucosa ratio was greater than 0.75 or the submucosa/total specimen ratio was greater than 0.42, then the diagnostic sensitivity and the specificity of the specimen for HD were 86.67% and 66.67%, respectively. Conclusion: In this prospective cross-sectional study, we demonstrated that RSB in diagnosing HD is a feasible, safe method with high sensitivity and specificity and low complication rates.